Dual Utilization of Lignocellulose Biomass and Glycerol Waste to Produce Fermentable Levoglucosan via Fast Pyrolysis - Zhang, Yingchuan; Xu, Feixiang; Chen, Fenglin; Zhang, Yanru; Wu, Yaxiang; Jiang, Liqun (Frontiers in Chemistry, 2022)
Glycerol waste was combined with microwave to pretreat lignocellulose before fast pyrolysis. After pretreatment, most alkali metal and alkaline earth metals (87.9%) and lignin (52.6%) were removed and a higher crystallinity was obtained. Comparatively, glycerol waste combined with microwave was proven to be more efficient than glycerol with conventional heating. During fast pyrolysis, higher content of levoglucosan in glycerol waste-pretreated products (27.5%) was obtained, compared to those pretreated by pure glycerol (18.8%) and untreated samples (5.8%). Production of fermentative toxic aldehyde and phenol by-products was also inhibited after glycerol waste-treatment. Following mechanistic study had validated that microwave in glycerol waste solvent could effectively ameliorate structure and components of lignocellulose meanwhile selectively removing lignin. Notably, under the optimal condition, the levoglucosan content in pyrolytic products was enhanced significantly from 5.8% to 32.9%. In short, this study provided an archetype to dually utilize waste resources for ameliorating lignocellulose structure and precisely manipulating complex fast pyrolysis.